Role of fatty acid binding proteins in pain signalling in rat dorsal root ganglia - Mat Harun, Noraihan; Bennett, Andrew J.; Chapman, Victoria (2016)
The main objective of this study is to investigate the interaction of FABPs with TRPV1 and PPARs in modulating nociceptive effects. The subpopulation distribution of these different types of FABPs and PPARs in rat DRG sections was determined by in situ hybridization (ISH) together with Taqman qPCR. In addition, protein-protein interactions of FABPs and PPARs in response to FABP activators and inhibitors need to be defined by Bimolecular fluorescence complementation (BiFC) assays. Furthermore, the differential effects of PPAR agonists on inflammatory genes induced by lipopolysaccharides or flagellin in rat DRG cultures were investigated by TaqMan Low Density Array (TLDA). ISH revealed that TRPV1 mRNA was mainly expressed in small-fiber neurons. However, the expression of FABPs and PPARs in different population of cells in DRG was not conclusive. Therefore, separation of neuronal and glial cells from mixed rat DRG culture was done to study the mRNA expression of FABPs and PPARs in this different type of cells. Meanwhile, TLDA showed PPAR agonists downregulate various inflammatory mediators after inflammatory induction via activation of TLR4 or TLR5 by LPS or flagellin, respectively. Most of the inflammatory genes were equally inhibited by all three PPAR agonists in LPSinduced group but unequally inhibited in flagellin-induced group which suggest the anti-inflammatory effects of PPAR agonists might be influenced by specific inflammatory signalling pathway.